THE RISK CONSEQUENCES AND INDONESIAN CAPITAL MARKET LIBERALIZATION TO INVESTMENT RETURN: STUDY ON LQ45 INDEX ON 2014-2018 - Suryadi, Irvan; Sundiman, Didi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Universal, 2022)
This study aims to determine the correlation of risk and Indonesian capital market liberalization to the return LQ45 index. This study used 248 samples of IHSG and LQ45 closing prices from Yahoo Finance in 2014-2018. The research belonging asset pricing studies with direct decomposition methods and qualitative combinations. This study proves (1) the value of idiosyncratic volatility has a significantly negative effect on return LQ45 index (2) systemic risk has a significant negative effect on return LQ45 index (3) capital market liberalization has a positive effect on returns LQ45 index. The research implication is a company with small idiosyncratic volatility will be preferred by investors unable to diversify portfolios.